Contribution of middle and new age kurdish state and principalities madrasahs to kurdish language and literature - EMİNOĞLU , Nevzat (Humanities Journal of University of Zakho, 2023)
At the emergence of the religion of Islam in the seventh century AD, the Kurds and their geography were stuck between the Persian and Byzantine Empires and were an area of contention. Starting from the middle of the 7th century, the Kurds began to experience a radical social change and dynamism with their acceptance of Islam. Thanks to the energy and social mobility and change stemming from this new belief and religion, the Kurds became active and active in general against their Christian neighbors, Greeks, Assyrians and Armenians, to whom they had been mostly passive, stagnant and passive. The new spirit and activity brought about by this change are political, economic, administrative, scientific, literary, etc. in Kurdish society. breakthrough in many ways. Thus, the Kurdish population and influence increased in their geography. The Kurds began to be influential outside the geography they were in. The Kurds came to power in the form of kingdoms and principalities in places outside their own lands. So much so that shortly after the Kurds became Muslims, they established three separate states in the same century. With this political domination they established under the names Shaddadi, Hasanveyhi and Hamdani, the Kurds began to be influential from Western Iran to the Caucasus. The lands of Western Iran and the geography of Mesopotamia, which was later called the fertile crescent, thus became the domain of several independent Kurdish dynasties. The period between the 10th and 12th centuries in the political history of the central lands of Islam deserves to be called the Kurdish centuries of Islam. For it was the Kurds who defended the central lands of Islam against the Byzantines, the Russians, and finally the Crusaders. A large and extensive reconstruction and construction activity was initiated by these Kurdish administrations. Developments and experiences were gained in many fields such as administration, bureaucracy, urbanism, trade, military service, science and literature among the Kurds. During this period, Kurdish governments built many mosques, fountains, bridges, castles, observatories, inns, Turkish baths, madrasas and hospitals in the geography of Kurdistan. The madrasahs, which were established in the period of the first Kurdish authorities, which started with the adoption of the Islamic religion by the Kurds and became widespread in the Kurdish society, played an important role as the production sites of the new religion and the theoretical teaching of the Islamic civilization that developed and became widespread depending on this religion. In addition, these educational institutions played an important role in the formation of a standard written language in Kurdish and in the development of Kurdish literature. These madrasahs, which were established by the Kurdish authorities, referred to as Kurdish madrasahs and functioned as basic educational institutions, have been one of the main pillars of political, scientific and literary development and breakthrough in the Kurds. Madrasahs, which served as the basic educational institution for the Kurdish society during the Middle Ages, are at the forefront of the dynamics that ensure political power and religious, cultural and linguistic unity in Kurds. The doctrine on which these educational institutions are based played a unifying role in the denominator of Ash'ari and Shafi'i sects within the understanding of Sunni Islam as a common religious identity among the Kurds. Our aim in this study is to investigate the contribution of the madrasahs, which were built and spread in the Kurdish states and principalities established in the middle and new ages, to the Kurdish language and literature. In this context, in our study, the adventure of the emergence of Kurdish madrasahs, the stages and periods of madrasas, the influence and contribution of madrasahs to the Kurdish language and literature will be discussed in detail. Although this issue is very important in terms of Kurdish history, identity and language, it has not been adequately and deservedly researched. This makes our study even more important.